Utility Demand-side Management for Solar Thermal Technology Transfer to Countries Subsidizing Electricity - Azeez, Nyaz Taher (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
Oil producing countries in the Middle East and North Africa (MENA) region have a common policy of offering higher energy subsidies compared to other countries. MENA countries depend on fossil fuels to meet their domestic energy needs. Supplying electricity to meet the demand in these countries requires a huge subsidy, placing an extensive burden on the available financial resources. Although solar thermal technologies have been generally proven to be economically feasible in many countries with abundant solar energy, MENA countries have yet to adopt these technologies to meet their energy needs. This is attributed to the low cost of electricity owing to higher subsidies, which have made it difficult for renewable technologies to penetrate these markets. Although previous research and international organizations have recommended the removal of energy subsidies as an approach to addressing the budget deficit crisis, these recommendations did not offer realistic solutions because the resources used for generating electricity are national resources, of which the people feel that they deserve to have a share. In the present study, demand-side management (DSM) programs promoting solar thermal technologies are proposed to overcome this problem. The methodology targets replacing electricity use with that of solar energy, reducing not only the electricity demand and the required subsidies but also the emissions of carbon dioxide and other harmful gases. Two case studies were conducted for the province of Erbil, (Kurdistan Region, Iraq) to develop the methodology. First, the economic feasibility of promoting solar water heaters (SWHs) by DSM was investigated. An estimated investment of US$90 million was required. The net present value (NPV) of installing the SWHs as part of a DSM program was US$776.6 million for a life cycle of 10 years. The program would have the advantage of reducing electricity sales (which are greatly subsidized) for preparing domestic hot water in 100,000 houses. Second, the benefits of replacing standard air conditioners with solar-assisted air conditioners through DSM were assessed for 100,000 offices, costing the utility US$80 million. It was found that a capacity requirement at an estimated cost of US$138 million would be avoided for at least 10 years. Furthermore, the program would help reduce consumer annual energy consumption by approximately 37%, thus removing the need for subsidies. It would be appropriate to differentiate between the two categories of countries in the MENA region, i.e., oil exporting countries and developing oil-producing countries. There would be differences in the DSM approach promoting solar thermal technologies between these two categories of countries as oil exporting countries have stronger financial reserves compared to developing oil-producing countries. Developing oil-producing countries, owing to a fiscal deficit and typically low quality power systems, face challenges in developing their infrastructure as well as meeting the high pre-tax subsidy. The proposed approach would have better implementation potential in developing oil-producing countries as it would facilitate deferral of the construction of new power plants and associated infrastructure; simultaneously, the electricity sales would be reduced significantly.

ÖZ: Orta Doğu ve Kuzey Afrika (MENA) bölgelerinde petrol üretimi yapan ülkelerin yaygın politikası diğer ülkelerle kıyaslandığında daha yüksek enerji sübvansiyonları vermeleridir. MENA ülkeleri, yurt içi enerji ihtiyaçlarını karşılamak için fosil yakıtlara bağımlıdır. Bu ülkelerde talebi karşılamak üzere elektrik temini için çok büyük sübvansiyonlar gereklidir ve bu da mevcut finansal kaynaklar üzerine muazzam bir yük bindirmektedir. Bol güneş enerjisi alan pek çok ülkede solar ısıl teknolojilerin genelde ekonomik olarak uygulanabilir olduğu kanıtlanmış olsa da MENA ülkeleri kendi enerji ihtiyaçlarını karşılamak için bu teknolojileri henüz benimsememişlerdir. Bu durum, yüksek sübvansiyonlar sayesinde elektriğin düşük maliyetli olmasına bağlanmaktadır ve bu da yenilenebilir enerji teknolojilerinin söz konusu pazarlara girmesini zorlaştırmıştır. Önceki araştırmalar ve uluslararası kuruluşlar bütçe açığı krizinin ele alınması için yaklaşım olarak enerji sübvansiyonlarının kaldırılmasını önermişlerse de bu öneriler, gerçekçi çözümler sunmamıştır çünkü elektrik üretiminde kullanılan kaynaklar ulusal kaynaklardır ve halk bu kaynaklarda payı olduğunu düşünmektedir. Bu çalışmada, bu sorunun üstesinden gelinmesi için solar ısıl teknolojileri destekleyen talep tarafı yönetimi (DSM) programları önerilmektedir. Kullanılan metodolojide, elektrik kullanımı yerine güneş enerjisi kullanılması hedeflenmekte ve böylece hem elektrik talebi ve gerekli sübvansiyonlar hem de karbondioksit ve diğer zararlı gazların emisyonları azaltılmaktadır. Metodolojinin geliştirilmesi amacıyla Erbil ili (Kürdistan Bölgesi, Irak) için iki örnek teknolojinin incelemesi yapılmıştır. İlk olarak, DSM ile solar su ısıtıcılarının (SWH) teşvikinin ekonomik uygulanabilirliği araştırılmıştır. Tahmini olarak 90 milyon Amerikan doları yatırım gerektiği tespit edilmiştir. DSM programının içinde SWH'lerin kurulmasının bugünkü net değeri (NPV) 10 yıllık bir döngüde 776,6 milyon Amerikan dolarıdır. Program, 100.000 eve sıcak kullanım suyu hazırlanmasında (büyük oranda devlet destekli olan) elektrik satışlarını azaltma avantajı sunacaktır. İkinci olarak, elektrik şirketine maliyetinin 80 milyon Amerikan doları olacağı öngörülen DSM ile standart klimaların solar destekli klimalar ile değiştirilmesinin yararı, 100.000 ofis için değerlendirilmiştir. Tahmini olarak 138 milyon Amerikan doları kadar maliyetli bir kapasite gerekliliğinin en az 10 yıl boyunca gerekmeyeceği bulunmuştur. Ayrıca program, yıllık enerji tüketimini %37 oranında azaltmaya yardımcı olacağından sübvansiyon ihtiyacını önemli ölçüde azaltacaktır. MENA bölgesindeki ülkeleri ikiye ayırmak uygun olur: petrol ihraç eden ülkeler ve gelişmekte olan petrol üreticisi ülkeler. Petrol ihraç eden ülkelerin, gelişmekte olan petrol üreticisi ülkelere kıyasla daha güçlü finansal rezervleri olduğundan solar ısıl teknolojilerin bu iki kategoriye tanıtılması için kullanılan DSM yaklaşımında farklılıklar olacaktır. Bütçelerinde bulunan mali açık ve tipik olarak düşük kaliteli enerji sistemleri nedeniyle, gelişmekte olan petrol üreticisi ülkeler altyapılarını geliştirme ve yüksek olan vergi öncesi sübvansiyonları karşılama konularında zorluklar yaşamaktadır. Önerilen yaklaşım yeni enerji tesislerinin ve bunlarla ilişkili altyapının yapımının geciktirilmesini kolaylaştıracağı ve elektrik satışları kayda değer oranda düşeceği için bu yaklaşımın gelişmekte olan petrol üretici ülkelerde uygulama potansiyeli daha iyi olacaktır.
Doctor of Philosophy in Mechanical Engineering. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Mechanical Engineering, 2019. Supervisor: Prof. Dr. Uğur Atikol.
Keywords: Mechanical Engineering; Solar Energy--Heat Engineering; Demand side management; solar thermal technology; Polysun software; solar water heater; electric water heater; solar assisted air conditioner; electricity subsidy; oil producing countries